Standards for Quality Assurance of Education in Kosovo According to European Higher Education Standards - Krasniqi, Safet (Integrated Journal for Research in Arts and Humanities, 2022)
In this paper I will address the challenges of Kosovo in a sector of social life, education. Addressing this topic is important for post-conflict societies that need help in building, establishing and making educational institutions functional. Ensuring the conditions for a quality education is related to the level of awareness and the need for educational planning. The work is focused on the possibilities of improving the quality of education, capacity building through local and international projects supported by the budget of Kosovo and the EU. The article begins with the analysis and planning process according to the SWOT program. Within the scientific methodology, research, material, historical, analytical and partially comparative methods were used. Theoretical and practical issues related to European strategies and standards will be elaborated, which increase the possibilities of achieving the objectives for ranking the education system of Kosovo in the direction of raising the quality of education.